2019
DOI: 10.1038/s41418-019-0403-9
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy role(s) in response to oncogenes and DNA replication stress

Abstract: Autophagy is an evolutionarily conserved process that captures aberrant intracellular proteins and/or damaged organelles for delivery to lysosomes, with implications for cellular and organismal homeostasis, aging and diverse pathologies, including cancer. During cancer development, autophagy may play both tumour-supporting and tumour-suppressing roles. Any relationships of autophagy to the established oncogene-induced replication stress (RS) and the ensuing DNA damage response (DDR)-mediated anti-cancer barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 72 publications
(102 reference statements)
1
50
0
2
Order By: Relevance
“…Stressors include both intrinsic factors, such as oxidative damage, telomere attrition, hyperproliferation, oncogene activation, and environmental sources, including UV-light, γ-irradiation, and chemotherapeutic drugs [18,19]. Regardless of their origin, the stress factors trigger DNA damage responses (DDR) in the affected cells, which can result in different outcomes, depending on the cell type and the extent of the damage [20].…”
Section: Senescence As Cellular Response To Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Stressors include both intrinsic factors, such as oxidative damage, telomere attrition, hyperproliferation, oncogene activation, and environmental sources, including UV-light, γ-irradiation, and chemotherapeutic drugs [18,19]. Regardless of their origin, the stress factors trigger DNA damage responses (DDR) in the affected cells, which can result in different outcomes, depending on the cell type and the extent of the damage [20].…”
Section: Senescence As Cellular Response To Stressmentioning
confidence: 99%
“…On the other hand, both physiological aging, characterized by telomere shortening, and long-term chronic stress, which impairs genomic integrity and stability, could lead to the activation of the senescence pathway [17]. In this sense, the senescence can be viewed as an adaptative response of cells and organisms when exposed to certain unfavorable environmental conditions.Stressors include both intrinsic factors, such as oxidative damage, telomere attrition, hyperproliferation, oncogene activation, and environmental sources, including UV-light, γ-irradiation, and chemotherapeutic drugs [18,19]. Regardless of their origin, the stress factors trigger DNA damage responses (DDR) in the affected cells, which can result in different outcomes, depending on the cell type and the extent of the damage [20].…”
mentioning
confidence: 99%
“…The origin of autophagosome membranes still remains controversial whereas autophagosome formation is regulated by two ubiquitin-like conjugation systems [170][171][172], Atg12-Atg5 and Atg8-PE. However, in contrast to mitophagy, autophagy is considered as a nonselective bulk degradative process where the autophagosomes randomly engulf contents in the cytosol [173,174]. Mitophagy induction and regulation are regulated by receptor-dependent or -independent pathways.…”
Section: Mitophagymentioning
confidence: 99%
“…This is based on the observation that an intact autophagy pathway correlates with decreased oxidative stress and increased genomic stability [8], thereby ensuring the survival of healthy, non-transformed cells. On the other hand, it was recently proposed that autophagy may also support cancer progression by facilitating tumor cell survival and fitness under replication stress, a common feature of most malignancies [21]. Adding a further layer of complexity, Nassour et al recently demonstrated that ACD can serve as a final barrier for oncogenic transformation during replicative crisis.…”
Section: Autophagy In Tumorigenesis and Tumor Progressionmentioning
confidence: 99%